Morality as the substructure of social justice: religion in education as a case in point - Ferdinand J Potgieter (South African Journal of Education, 2011)
Moral issues and principles do not only emerge in cases of conflict among, for instance, religious communities or political parties; indeed they form the moral substructure of notions of social justice. During periods of conflict each opponent claims justice for his/her side and bases the claim on certain principles. In this article, reference is made to the differences among South Africans about the extent to which religion and religious differences in the population should be accommodated in public school education. Explorativehermeneuticphenomenologyfacilitates an investigation into the nexus between social justice and its moral substructure. This is followed by a discussion of the moral dilemma facing education policymakers regarding the accommodation of religion in public education, with the aid of two contrasting metaphors, namely, the Strict Father and the Nurturant Parent.